“Common Factors” and cointegration of Japan’s aggregate import demand function: An Empirical Study / Tang Tuck Cheong - Tang, T.C. (2012)
It is well documented in the literature that Japan’s aggregate demand for imported goods and services is determined by income and relative price of imports. However, the findings based on cointegration methods are mixed and to some extent conflicting. The aim of this study is to examine the influence of a set of “common factors” on the empirical evidence of the long-run behavior of import demand relationship, and to identify whether any of the “common factors” are responsible for the ambiguous results reported in the literature. Three major candidate “common factors” have been empirically identified from the relevant literature and the data obtained from previous studies for Japan. These are data frequency, the choice of domestic activity variable and the cointegration testing method. The sample period of the present investigation covers nearly four decades, extending from 1970 to 2007. The empirical results demonstrate that the three “common factors” do simultaneously explain the divergent findings of cointegratedness of Japan’s aggregate import demand function as well as the differences in the long-run elasticity estimates. The study yields some empirical support for the conclusion that the testing technique is the main factor that explains the divergence in cointegration findings for Japan’s import demand relation. Generally speaking, the existing empirical studies of long run aggregate import demand have indiscriminately employed the standard empirical specifications, the latest cointegration tests and the updated data available. The significance of this study derives from the fact that the cointegration findings for Japan’s aggregate import demand function convey useful information to policymakers for formulating Japan’s trade policies. More explicitly, the long-run responses of imports of goods and services to their macroeconomic determinants (real income and relative price) support the view that fiscal policy and exchange rate policy would be effective in influencing Japan’s external imbalances. On the other hand, the open economy macro equilibrium perspective shows that the financial sector (financial factors) also plays a role in determining the aggregate demand for imports. Aggregate import demand functions derived from this general equilibrium model are supported by positive cointegration findings from Japan’s data. The cointegratedness of the general equilibrium equations as well as the estimated elasticities of domestic activity and relative price are also influenced by the “common factors” and their interactions.